2006
DOI: 10.1007/s00192-005-0044-z
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of periurethral blood flow resistive indices and urethral closure pressure of incontinent women

Abstract: This study correlated Doppler resistive indices (RIs) with maximum urethral closure pressures (MUCPs) in women with stress urinary incontinence. We hypothesized that urethral blood flow would be inversely correlated to urethral closure pressures. Fifty-three women underwent spectral Doppler waveform analyses of periurethral vasculature to calculate RI. Urethral morphology including pubovesicular length (PVL) with and without cough was measured. MUCPs were obtained according to International Continence Society … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
(26 reference statements)
1
5
0
Order By: Relevance
“…Hence, decreased collagen I/III ratio is associated with reduced urethral and anal canal closure function [7,[13][14][15]. Both estrogen deficiency and ageing independently and negatively influences the submucosal urethral and anal canal blood vessel counts and collagen I/III ratio in anatomical, experimental and clinical studies, similar to our findings [4,11,12,14,15]. In fact, ghrelin and its receptor are expressed in human microvascular endothelial cells and rat osteoblasts where ghrelin stimulates endothelial cell proliferation, migration, and angiogenesis as well as osteoblastic synthesis of collagen type I, as seen in this study [19,20].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Hence, decreased collagen I/III ratio is associated with reduced urethral and anal canal closure function [7,[13][14][15]. Both estrogen deficiency and ageing independently and negatively influences the submucosal urethral and anal canal blood vessel counts and collagen I/III ratio in anatomical, experimental and clinical studies, similar to our findings [4,11,12,14,15]. In fact, ghrelin and its receptor are expressed in human microvascular endothelial cells and rat osteoblasts where ghrelin stimulates endothelial cell proliferation, migration, and angiogenesis as well as osteoblastic synthesis of collagen type I, as seen in this study [19,20].…”
Section: Discussionsupporting
confidence: 79%
“…We have previously reported that estrogen and ghrelin administration, separately or in combination, in middleaged ovariectomized Wistar rats significantly reversed the ovariectomy-induced decrease in submucosal urethral and anal canal vessel counts [11]. This is an important mechanism of urinary and fecal control in women [11,12]. We did not, however, compare the effect of both hormones on postovariectomy vessel number in old as opposed to young adult rats.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…However, a Doppler blood flow study recorded the blood flow resistive index as well as MUCP in female patients and concluded that blood flow resistive index did not correlate with closure pressure or subjective complaints of incontinence. 29 The UP profile in human studies is measured using a water perfused side hole or solid-state microtip transducer that is pulled across the urethra at a constant speed. The UP profile is a bell-shaped curve with peak pressure, also called MUCP, located in the middle of the urethra.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies performed with the use of spectral doppler in TPUS assessment of the urethral vascularity in incontinent multiparous have shown contradictory results i.e. RI was not correlated with parity (Hall et al 2006). In the study by Siracusano et al (Siracusano et al 2001) colour doppler ultrasound of the female urethra in normal fertile young women identified a significantly greater RI in the proximal urethra compared to the middle and distal urethra.…”
Section: Discussionmentioning
confidence: 99%